Household Savings in Germany - Axel Borsch-Supan; Anette Reil-Held; Ralf Rodepeter; Reinhold Schnabel; Joachim Winter (Levy Economics Institute of Bard College, 2000)
This paper describes how German households save and how their saving behavior is linked to public policy, notably pension policy. The analysis is based on a synthetic panel of four cross sections of the German Income and Expenditure Survey ("Einkommens- und Verbrauchsstichproben," EVS,1978, 1983, 1988, and 1993). The paper carefully distinguishes between several saving measures and concepts. It separates discretionary savings from mandatory savings and uses two flow measures: first, the sum of purchases of assets minus the sum of sales of assets and, second, the residual of income minus consumption. Our main finding is a hump-shaped age-saving profile with a high overall saving rate. However, savings remain positive in old age, even for most low-income households. How can we explain what may be termed the "German savings puzzle"? Germany has one of the most generous public pension and health insurance systems in the world, yet private savings are high until old age. We provide a complicated answer that combines historical facts with capital market imperfections and a distinction between the role of discretionary and mandatory savings.
Keywords: 330